Suspended sediment concentrations in Alpine rivers: from annual regimes to sub-daily extreme events - A. van Hamel; A. van Hamel; A. van Hamel; P. Molnar; J. Janzing; J. Janzing; J. Janzing; M. I. Brunner; M. I. Brunner; M. I. Brunner (Hydrology and Earth System Sciences)
The occurrence of extreme suspended sediment concentrations (SSCs) in rivers can have negative impacts on human infrastructure, water quality, and the health of aquatic ecosystems. However, most existing studies have focused on the SSC dynamics of individual catchments or single events. Consequently, large-scale patterns of suspended sediment dynamics remain poorly understood. The objective of this study is to identify spatial differences in (1) the seasonality of SSCs and (2) the occurrence of SSC extremes in the Alps. For our analyses, we use 10 years of observed sub-daily SSC data from 38 gauging stations in Switzerland and Austria.